Inclusivity-Based Management: Building Diversified and Collaborative Work Teams - Azhmy, Muhammad Fauzan; Ray, Qonita (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The purpose of this research is to discuss inclusive-based management as an essential approach in building diversified and collaborative teams within an organization. Diversity has gained increasing attention in the ever-changing and complex business environment. In this context, inclusive-based management offers a holistic approach to appreciate and leverage the diversity of team members as valuable assets in achieving organizational goals. This research employs literature review and data analysis from various relevant sources. The literature review is conducted to understand the concept of inclusivity in management and effective strategies to create diversified and collaborative teams. Additionally, contemporary data and information on the benefits of inclusivity in enhancing productivity, innovation, and collaboration in organizations are analyzed to present reliable outcomes. The results of this research demonstrate that inclusive-based management can have a positive impact on forming diverse and collaborative teams. An inclusive approach in management empowers every team member, regardless of their background or personal characteristics, thus creating an inclusive, fair, and supportive work environment. The findings also reveal that team diversity enhances creativity, innovation, and productivity, while improving the team's capacity to navigate external changes and challenges.